SIAVA: Secret Information Aggregation Design for Various Applications in Wireless Sensor Networks - Ezhilvendan, M.; Kavitha, T.; Chinnadurai, S.; Kumaran, P. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In general information aggregation design that reduces a large amount of transmission is the most practical technique. In previous studies, homomorphic encryptions have been applied to conceal communication during aggregation such that enciphered data can be aggregated algebraically without decryption. Since aggregators collect data without decryption, adversaries are not able to forge aggregated results by compromising them. However, these schemes are not satisfy multi-application environments. Second, these schemes become insecure in case some sensor nodes are compromised. Third, these schemes do not provide secure counting; thus, they may suffer unauthorized aggregation attacks. Therefore, we propose a new concealed data aggregation scheme extended from Boneh et al.s homomorphic public encryption system. The proposed scheme has three contributions. First, it is designed for a multi-application environment. The base station extracts application-specific data from aggregated cipher texts. Next, it mitigates the impact of compromising attacks in single application environments. Finally, it degrades the damage from unauthorized aggregations. To prove the proposed schemes robustness and efficiency, we also conducted the comprehensive analyses and comparisons in the end.